Domestic counter-terrorism in a global world post-9/11 institutional structures and cultures in Canada and the United Kingdom - Alati, Daniel (Routledge research in terrorism and the law, 2018)
This book explores these changes to counter-terrorism laws and policies in the United Kingdom and Canada in order to demonstrate that despite the force of international legal instruments, including the heavily scrutinized UN Security Council Resolution 1373, the evolution of counter-terrorism policies in different jurisdictions is best analysed and understood as a product of local institutional structures and cultures.